2009
DOI: 10.1186/1471-2407-9-173
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of differentiation 4 (Id4) is a potential tumor suppressor in prostate cancer

Abstract: BackgroundInhibitor of differentiation 4 (Id4), a member of the Id gene family is also a dominant negative regulator of basic helix loop helix (bHLH) transcription factors. Some of the functions of Id4 appear to be unique as compared to its other family members Id1, Id2 and Id3. Loss of Id4 gene expression in many cancers in association with promoter hypermethylation has led to the proposal that Id4 may act as a tumor suppressor. In this study we provide functional evidence that Id4 indeed acts as a tumor supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 72 publications
(103 reference statements)
11
91
1
Order By: Relevance
“…In apparent contrast to this inhibitory role for the Id family of genes, a more limited number of observations have suggested a role for ID family members in supporting lineage-specific differentiation (18,22,34,36,37). Both ID2 and ID4 have been shown to be induced in various cell culture systems during adipocyte differentiation in vitro (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…In apparent contrast to this inhibitory role for the Id family of genes, a more limited number of observations have suggested a role for ID family members in supporting lineage-specific differentiation (18,22,34,36,37). Both ID2 and ID4 have been shown to be induced in various cell culture systems during adipocyte differentiation in vitro (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…11 Members of this family lack a DNA binding domain but retain the ability to bind and thus inhibit the function of other bHLH proteins. Such binding predominately results in a tumor suppressor role of ID4 in colorectal, 12 prostate, 13,14 and gastric 15 cancers, whereas in breast 16 and bladder 17 cancer, it has oncogenic features. [16][17][18] In a study that used an interleukin-15 transgenic mouse model of natural killer (NK) cell leukemia, the authors demonstrated that ID4 was silenced by methylation in transformed lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…ID4 acts as a tumour suppressor, for example, in the normal prostate where it is highly expressed; this expression decreases in prostate cancer in a stage-dependent manner as a result of ID4 promoter hypermethylation (Carey et al 2009, Sharma et al 2012. High-grade tumours are associated with the absence of ID4 expression (Carey et al 2009, Sharma et al 2012. In this context, ID4 exerts anti-proliferative effects, in part, by increasing expression of the classical tumour suppressor genes p27 and p21 (Carey et al 2009).…”
Section: Id4 Controls Malignancy In Blbcmentioning
confidence: 99%
“…ID4 effects varied outcomes in cell proliferation and differentiation depending on the availability of cofactors, and hence, play either a tumour suppressive or oncogenic function. ID4 acts as a tumour suppressor, for example, in the normal prostate where it is highly expressed; this expression decreases in prostate cancer in a stage-dependent manner as a result of ID4 promoter hypermethylation (Carey et al 2009, Sharma et al 2012. High-grade tumours are associated with the absence of ID4 expression (Carey et al 2009, Sharma et al 2012.…”
Section: Id4 Controls Malignancy In Blbcmentioning
confidence: 99%
See 1 more Smart Citation